Kekuatan Fleksural Dentin setelah Eksposur Semen Bioaktif - Evelyna, Angela; Tresna Wulan Sari, Lia Amelia; Ma’rup, Fathul Mauludy (Ikatan Peminat Ilmu Material dan Alat Kedokteran Gigi (IPAMAGI), 2022)
Bioactive cements are used widely in dentistry, especially in restorative and endodontic field. Bioactive cement can induce response from living tissue, organism, or cells by hydroxyapatite layers formation when in contact with tissue fluid. Despite of its benefit, bioactive cements use as root canal medicament can caused dentinal collagen damage that can lead to tooth fracture. This literature study objective is to analyse dentinal flexural strength after bioactive cements exposure by literature study. Literature study results show that every bioactive cement exposure can decrease dentin flexural strength that can lead to root canal treatment failure. Bioactive cement composition that effect dentin flexural strength in long term use is Calcium Hydroxide. Long term clinical test of bioactive cement from different generation need to be evaluated on next study.